PENGEMBANGAN FILM ANIMASI 3 DIMENSI â€œTUDE THE MOVIE â€“ PETUALANGAN SI RINA (TERTANGKAPNYA BURUNG JALAK BALI)â€ - Yoga Antara, I Made; Crisnapati, Padma Nyoman; Agus Wirawan, I Made; Gede Sunarya, I Made (Universitas Pendidikan Ganesha, 2018)
The development of this 3d animation movie called â€œTude The Movie â€“ Petualangan Si Rinaâ€ (Tertangkapnya Burung Jalak Bali), is second part of five parts on 3d animation movie called â€œTude The Movie â€“ Petualangan Si Rinaâ€. The story of these series are not only about the preparation of Pandu to hangout with his friends but also about bad guy that catches Jalak Bali in a wild and the bad guy also want to sell the Jalak Bali to a buyer that already ordered it. The objective of this research : 1) To design 3d animated film â€œTude The Movie â€“ Petualangan Si Rina (Tertangkapnya Burung Jalak Bali)â€. 2) To implement 3d animated film â€œTude The Movie â€“ Petualangan Si Rina (Tertangkapnya Burung Jalak Bali)â€.In making this movie, the method of the research or the movie designed using Block Diagram. Block Diagram explain the steps of creating the 3d animated film Tude The Movie from beginning until finishing. In Block Diagram, there were 3 main stages 1) Pre Production (Story Idea, Writing and Creating the Storyboard), 2) Production (Modeling, Texturing, Rigging, Skinning, Acting/Animation, Lighting, Andrendering) 3) Post Production (Vioce Recond and Editing)The result of this research was 3d animated film on DVD format. This movie has been successfully completed in accordance with the design made earlier.